Trends and cross-country inequalities in dengue, 1990–2021 - Mingzhu Zhou; Yong He; Liangmiao Wu; Kaiyuan Weng (PLoS ONE, 2025)
Background The existing body of literature is deficient in the most recent data regarding the global perspective of dengue fever and its associated health inequities.Our aim is to assess the global burden of dengue fever and its health inequities from 1990 to 2021. Methods The Global Burden of Disease (GBD) database, organized by global health research institutions, is a comprehensive database and the largest-scale and most detailed scientific research to date. We utilized the GBD database for epidemiological trends, demographic analysis, epidemiological decomposition, cross-national inequality and predictive modeling for the global dengue burden up to 2051 were also performed. Results Globally, dengue fever incidence, prevalence, Disability-Adjusted Life-Years (DALYs), and mortality have risen with marked international disparities. From 1990 to 2021, Age-Standardized Rates (ASRs) for incidence and prevalence rose by 1.83% (95% CI: 1.58%–2.08%), and for DALYs and mortality by 1.33% (95% CI: 1.10%–1.57%) and 1.70% (95% CI: 1.45%–1.94%), respectively. Age-Period-Cohort (APC) model analysis showed a positive link between dengue fever incidence and age, with mortality spiking in those over 80. DALYs burden decomposition highlighted population growth as the key driver of global burden, yet impacts differed across Socio-Demographic Index (SDI) quintiles. Dengue fever burden inequalities related to SDI have remained, with benefits shifting from poor to rich populations. Bayesian Age-Period-Cohort (BAPC) model projections indicate stable incidence and prevalence ASRs, but declining DALYs and mortality ASRs, especially for females. Conclusion This study elucidates the changes in the burden of dengue fever against the backdrop of a burgeoning global population, severe aging, and pronounced health inequities across nations, quantifying these alterations and forecasting the trends in the disease burden over the next three decades. Concurrently, the research proposes effective measures for various countries and regions to mitigate health inequities.